2010
DOI: 10.1056/nejmoa1000678
|View full text |Cite
|
Sign up to set email alerts
|

Early Palliative Care for Patients with Metastatic Non–Small-Cell Lung Cancer

Abstract: Among patients with metastatic non-small-cell lung cancer, early palliative care led to significant improvements in both quality of life and mood. As compared with patients receiving standard care, patients receiving early palliative care had less aggressive care at the end of life but longer survival. (Funded by an American Society of Clinical Oncology Career Development Award and philanthropic gifts; ClinicalTrials.gov number, NCT01038271.)

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

100
4,864
23
193

Year Published

2011
2011
2021
2021

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 6,352 publications
(5,296 citation statements)
references
References 37 publications
100
4,864
23
193
Order By: Relevance
“…Temel and colleagues study [8] demonstrated the benefits of good end of life care. In a randomised controlled trial, patients with metastatic non-small cell lung cancer (and thus a poor prognosis) were randomised to receive standard oncological treatment with or without early referral, i.e.…”
Section: Introductionmentioning
confidence: 99%
“…Temel and colleagues study [8] demonstrated the benefits of good end of life care. In a randomised controlled trial, patients with metastatic non-small cell lung cancer (and thus a poor prognosis) were randomised to receive standard oncological treatment with or without early referral, i.e.…”
Section: Introductionmentioning
confidence: 99%
“…The discipline's clinical roots have been most well established in and around oncology care. Over recent decades, the timing of palliative care involvement has gradually marched upstream in disease trajectory from exclusive focus on end-of-life care toward much earlier implemented concurrent care, such as the time of metastatic disease staging [2]. Additionally, clinical models of palliative care continue to evolve across care settings.…”
Section: Originsmentioning
confidence: 99%
“…Prior studies show that patients often have inaccurate perceptions about prognosis, leading to receipt of burdensome treatments at the end of life, 10,11 that patients may alter end-of-life treatment requests when adequately informed, 12 and that outcomes may be improved when patients engage in palliative care. 13 General internists are well positioned to offer a clinical perspective on the overall health status of those with advanced cancer and to discuss end-of-life care. 14 The general internist may also be well suited to revisit prognosis and realign the care plan with patient preferences.…”
Section: Recommendations 1 and 2: Engaged Patientsmentioning
confidence: 99%